'A scene is just a marketing tool': alternative income streams in porn's gig economy. Issue 2 (2nd April 2016) - Berg, Heather
ABSTRACT: Drawing from ethnographic fieldwork and interviews, this article explores the role of alternative income streams in the political economy of the US adult film industry. For many porn workers, film scenes function more as marketing tools – advertisements for workers' other paid pursuits – than primary sources of income. They represent one way for performers to creatively manipulate the conditions of porn work in order to maximize earning potential, resist burnout by varying job tasks, and otherwise exert control over their work life. At the same time, alternative income streams help to maintain the current structuring of porn performance by sustaining a reserve army of labour motivated to perform even if pay and working conditions are poor. Finally, alternative income streams place workers in shifting positions as entrepreneurs, independent contractors, employees, contracted and freelance managers, and producers. This article considers what such relations tell us about the workings of class in the porn industry.